2020
DOI: 10.1002/agj2.20414
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop biomass production across establishment methods in mid‐Atlantic corn

Abstract: Drill-interseeding, broadcast-interseeding, and post-harvest drilling for establishment of overwintering cover crops after no-till corn (Zea mays L.) each present distinct challenges and benefits. Experiments were conducted at the Beltsville Agricultural Research Center (Beltsville, MD) across three growing seasons (2013-2014, 2014-2015, 2015-2016) to evaluate the relative performance of these three establishment methods across four cover crop treatments: (a) cereal rye (Secale cereale L.), (b) annual ryegrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…Although soil moisture at our study site may not have been sufficient for optimum growth of rye, our rye was not a failed crop because the amount of rye biomass in this study was consistent with, or greater than, aboveground dry biomass for overwintered rye in previous studies (Bavougian et al ., 2019; Toom et al ., 2019; Moore and Mirsky, 2020; Baxter et al ., 2021). However, rye biomass in our study was less than the amount of rye biomass reported by Wayman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although soil moisture at our study site may not have been sufficient for optimum growth of rye, our rye was not a failed crop because the amount of rye biomass in this study was consistent with, or greater than, aboveground dry biomass for overwintered rye in previous studies (Bavougian et al ., 2019; Toom et al ., 2019; Moore and Mirsky, 2020; Baxter et al ., 2021). However, rye biomass in our study was less than the amount of rye biomass reported by Wayman et al .…”
Section: Discussionmentioning
confidence: 99%
“…Light transmission data were collected only at the time of interseeding to define environmental conditions. However, previous research has identified sunlight penetration through cash crop canopy as a limiting factor for growth of interseeded cover crops (Curran et al., 2018; Mohammed et al., 2020; Moore & Mirsky, 2020). Future trials could use light transmission as a treatment factor to determine the lowest light transmittance at which the interseeded cover crops are still likely to successfully establish.…”
Section: Discussionmentioning
confidence: 99%
“…Previous field trials of interseeding cover crops into full‐season soybean and corn have demonstrated an inverse relationship between cover crop and cash crop performance; in fields with optimal cash crop vegetative growth, the cover crops were unable to survive under the dense soybean or corn canopy through the summer and fall (Caswell et al., 2019; Uchino et al., 2009; Youngerman et al., 2018). Canopy closure is particularly problematic in warmer climates where the crop canopy closes quickly and there are often dry weather conditions during maturation (Moore & Mirsky, 2020). Interseeding cover crops later in the soybean season benefits the cover crop by shortening the length of time it must survive under the soybean canopy (Mohammed et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Early cover crop planting can be accomplished by interseeding cover crops into standing cash crops (Fisher et al 2011;Wilson et al 2013;Moore and Mirsky 2020). Cover crops can be broadcast interseeded using high-clearance ground-based air-seeding equipment or by airplane.…”
mentioning
confidence: 99%
“…However, drilling also usually requires waiting until the cash crop has been removed by harvest, which typically occurs a month or more after cover crops could be interseeded. Heat and shade tolerant cover crops can be interseeded into young vegetative corn early in summer using specialized high-clearance drills (Moore and Mirsky 2020), but emergence and growth may be inconsistent (Curran et al 2018;Noland et al 2018;Brooker et al 2020). Cover crop seedling emergence after broadcast interseeding is dependent upon rainfall or irrigation after sowing (Fisher et al 2011;Wilson et al 2013;Haramoto 2019;Moore and Mirsky 2020).…”
mentioning
confidence: 99%